Ethnological Notes on the Cameroon (1916) (Colonial Letters and the Contact of Knowledges, 1916)
This file contains colonial ethnological notes on Cameroons written by Meyer, Das Deutsche Kolonialreich
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies